MANAJEMEN SUMBER DAYA MANUSIA (MSDM) DI SMP PLUS AL-ISHLAH - Shofyan, Hilmi (As-Sulthan Journal of Education, 2024)
Effective Human Resource Management (HRM) is critical in education, especially in teacher management. Qualified and professional teachers play a direct role in the success of learning, so teacher HR management must be carried out carefully to ensure optimal teaching quality. This study uses a descriptive qualitative approach with a case study method, focusing on human resource management (HRM) at SMP Plus Al-Ishlah and its impact on teaching quality. Data were collected through in-depth interviews, observations, and documentation, with research subjects including the principal and teachers. Source triangulation was carried out to increase the validity of the results, comparing data from interviews, observations, and HRM policy documents. Data analysis used the Miles and Huberman interactive model, including data reduction, data presentation, and concluding. The results of this study indicate that Human Resource Management (HRM) at SMP Plus Al-Ishlah focuses on teacher management to improve the quality of education. The process begins with teacher needs planning, strict selection through tests and interviews, and ongoing training such as workshops to improve teaching skills. Performance assessments are carried out systematically to ensure teacher professionalism. A conducive work environment is also built through a spirit of togetherness and openness, supporting teachers to continue to develop and commit. This approach ensures that the quality of education is maintained through the dedication of professional teachers.